9514 1404 393
Answer:
g = 1/6(w+40)
Step-by-step explanation:
The given equation is already solved for g. Nothing need be done.
g = 1/6(w+40)
Answer:
Step-by-step explanation:
You might find this easier if you change h(x) to y. It might look more familiar.
you are given 1 point and that is (-1,1). What that means is when x = -1,
y = 1
You have written this as though y is linear. It is not. The power is 1/3, not 1.
Let us try B which is what I think the answer is.
y = (x + 2)^(1/3)
Put x = -1 on the right hand side.
y = (-1 + 2)^(1/3)
y = (1)^(1/3)
The cube root of 1 is 1.
So the answer is
y = (x + 2)^(1/3)
It's a conditional probability
P( getting a given number AND getting again the same number)
P(of getting any number) =1/6
P(of getting once again the same number) 1/6 x 1/6 = 1/36
Answer:
1 / 7 (x - 2)
Step-by-step explanation:
x - 2 / 7(x - 2)^2
= (x - 2) / 7 (x - 2) (x - 2)
= 1 / 7 (x - 2)
58 212 2800 900
/ \ / \ / \ / \
29 2 2 106 700 4 3 300
/ \ / \ / \ / \
2 53 70 10 2 2 3 100
/ \ / \ / \
7 10 5 2 2 50
/ \ / \
5 2 5 10
/ \
5 2
The prime factors are in bold.